2020
DOI: 10.3390/jcm9030688
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Digital and Conventional Full-Arch Impressions in Patients: An Update

Abstract: The aim of this clinical study was to update the available data in the literature regarding the transfer accuracy (trueness/precision) of four current intraoral scanners (IOS) equipped with the latest software versions and to compare these data with conventional impressions (CVI). A metallic reference aid served as a reference dataset. Four digital impressions (Trios3Cart, Trios3Pod, Trios4Pod, and Primescan) and one CVI were investigated in five patients. Scan data were analyzed using three-dimensional analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
1
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 31 publications
4
80
1
11
Order By: Relevance
“…The direct digitization of the dentition by means of an intra-oral scanner is at least as accurate as the indirect digitization of gypsum study casts using a lab scanner [66,67]. The use of an intra-oral scanner could have improved the precision and would have simplified the protocol [68,69]. Moreover, it has been reported that the use of digital measurements, by comparing superimposed virtual casts, is more reliable and consistent compared to conventional measurements [70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…The direct digitization of the dentition by means of an intra-oral scanner is at least as accurate as the indirect digitization of gypsum study casts using a lab scanner [66,67]. The use of an intra-oral scanner could have improved the precision and would have simplified the protocol [68,69]. Moreover, it has been reported that the use of digital measurements, by comparing superimposed virtual casts, is more reliable and consistent compared to conventional measurements [70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…O'Toole et al [45] investigated different alignment procedures and showed significantly lower alignment errors for reference alignment compared to best-fit alignment. In the oral cavity, there is no reference structure, so some studies used additional reference aids [46,47]. However, this is not applicable for measurement in daily practice without expert skills or a complex laboratory setup.…”
Section: Discussionmentioning
confidence: 99%
“…Another questionable factor that could affect the scan is the type of substrate. The type of scanned tissue (substrate) does not impact the overall accuracy of intraoral scans, which is a hypothesis that was confirmed by researchers from South Carolina in 2019 [ 15 ]. However, researchers from the same region, but a year later, claimed that the type of substrate does affect the trueness and precision of a scan.…”
Section: Discussionmentioning
confidence: 81%